Synthesis and characterization of bio resin from palm oil - Beg, M. D.H.; Jamari, Saidatul Shima; Yunus, Rosli Mohd
Vegetable oil is one of the renewable bioresources which can be used as an alternative of petroleum-based raw materials for the preparation of polymeric materials. In this research work, polyalkyd-based resin was prepared from palm oil by using polycondensation reaction. A two-step method viz. alcoholysis and esterification was conducted to synthesize polyalkyd-based resin,. Prior to alcoholysis, crude palm oil was subjected for catalytic dehydration process to increase its unsaturation for the preparation of good quality alkyd resins. Five different catalysts such as sulphuric acid, para-toluene sulfonic acid, phosphoric acid, sodium hydrogen sulphate and potassium hydrogen sulphate were used for the dehydration of palm oil. In alcoholysis process, the triglyceride-based dehydrated oil was reacted with glycerol to produce monoglyceride. The optimum condition was used to prepare different types of alkyds by using five different types of acid anhydrides such as maleic anhydride, phthalic anhydride, succinic anhydride, 3,4,5,6-tetrahydrophthalic anhydride and cis-1,2-cyclohexanedicarboxylic anhydride. A comparison was drawn among the resins prepared by using different anhydrides. Comparison was also drawn in between aliphatic and aromatic anhydride containing resins. The produced bioresins were characterized for physico-chemical properties such as viscosity, density, iodine value, acid value, saponification value, drying time, non-volatile materials content, specific gravity, colour, etc. The resins prepared from optimum reaction parameters were subjected for curing process by using methyl ethyl ketone peroxide (MEKP), as initiator, and cobalt naphthanate, as dryer. To enhance the resinous property, multi-walled carbon nanotubes were dispersed into the resin at different percentages of loading such as 0.5, 1.0 and 1.5 wt.%. The filler loading was optimized regarding the end properties of the film produced by incorporating them. Finally, in-situ polymerization with carbon nanotubes during esterification was performed by adding optimum percentage of loading. A comparison of the properties of the films was drawn among the optimum loaded nanotube-based film, in-situ reacted nano-tube based film and the films with different percentages of loading and that of without using carbon nano tube. The films were characterized by different testing such as adhesion, chemical resistivity, thermogravimetric analysis, differential scanning calorimetry, field-emission scanning electron microscopy, x-ray diffraction analysis, contact-angel measurement, tensile testing, elongation at break, pencil hardness, gloss etc. Finally, the curing kinetics of the resin was analysed to evaluate the kinetic parameters such as reaction rate, activation energy, degree of conversion in terms of time and temperature. Result analyses through RSM revealed a desirability of 0.985, predicted reaction time of 88.64 min, catalyst concentration of 0.04 wt.%, agitation speed of 584.20 rpm and phthalic anhydride: mono-glyceride (PA:MG) molar ratio of 0.35:1 at reaction temperature 240oC. Moreover, 91.5% fractional conversion was achieved actually, which is close to the predicted value. Analysis revealed that 3,4,5,6-tetrahydophthalic anhydride (TPA)-based resin shows improved resinous property than that of others due to high degree of crosslinking. It was also found that higher amount of aliphatic anhydrides are responsible for high degree of crosslinking density, whereas higher thermal stability was ensured by the inclusion of aromatic anhydride. Finally, incorporation of multi-walled carbon nanotubes (MWCNTs) into the optimum alkyd resin enhanced the overall resinous properties, which boosted up significantly through in-situ reaction. From this project 6 Journals papers, 4 conference papers and 1 patent has been published.